(Ø§Ù„Ø¹Ø§Ø¯Ø©ÙŠÙˆÙˆØ§Ù†Ø¬Ø¹Ø§Ù†ØªÙŠÙ†ÙÙŠÙ†Ø¸Ø±Ø§Ù„Ø£ØÙƒØ§Ù…Ø§Ù„Ø´Ø±ÙŠØ¹Ø©Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© (Ø¯Ø±Ø§Ø³Ø©Ù…ÙŠØ¯Ø§Ù†ÙŠØ© :ØÙˆÙ„Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ÙƒØ§Ø¬ÙŠØ¬Ø§Ù†Ø¬Ø¥Ø³Ù„Ø§Ù…Ø¨ÙˆØ¹Ø§ÙŠØ©ÙƒØ§Ø¹ÙŠÙ†Ø¨Ø§Ø¨Ø§Ù†Ø¯Ø§Ù…ÙƒØ§Ø±Ø§Ù†Ø¬Ø§Ø³Ø§Ù…Ø¨Ø§Ù„ÙŠ - Khalid, Idham; Anshori, Isa; Masduqi, Ahmad (Muhammadiyah University of Surabaya, 2020)
ABSTRACTIn the Balinese community, especially the people in the Kecicang Islam Village of Bungaya Village Kangin Bebandem Karangasem, there is a tradition in the marriage process called